The effect of culture and religion on the implementation of comprehensive sexuality education in selected primary schools of Zambia - Mukonka, Remmy; Mushibwe, Christine; Jacobs, Choolwe (Eureka: Journal of Educational Research, 2023)
Despite full-scale implementation of Comprehensive Sexuality Education (CSE) in Zambia, behavioural health problems among adolescents persist which include early and unprotected sex, sexual abuse, early marriages and teenage pregnancies. The study aimed at establishing the effect of culture and religion on the implementation of CSE in selected primary schools of Kabwe, Lusaka and Choma districts of Zambia. The study utilised mixed method design with a pupil population drawn from 9 selected primary schools. The sample size of the study was 700 adolescents (aged 12–17 years) and 16 key informants i.e. headteachers, teachers, guidance and counseling teachers, and government senior officials). Simple random sampling was utilised to select pupils while purposive sampling was employed to select key informants. Interview guides, questionnaires and focus group discussions were employed to collect statistical and narrative data. Data was analysed using a Statistical Package for Social Sciences (SPSS) and thematic analysis. The study found that culture and religion influenced the implementation of CSE in selected primary schools. This was evident in the language used for teaching CSE, where vernacular expressions of sexuality faced resistance in a culturally conservative society, despite the dominant use of English. Additionally, there was a perception of incompatibility between religious beliefs and teaching sexuality to adolescents. Moreover, adult respondents believed that CSE could breach the moral fabric. In conclusion, for CSE to achieve its goal of improving young people's education and health outcomes, both religious and traditional leaders must be involved in its implementation.